DO WORLD GOLD PRICE, DOW JONES ISLAMIC MARKET AND INFLATION AFFECT THE PERFORMANCE OF JAKARTA ISLAMIC INDEX? - Janitra, Egan (Jurnal Ekonomi & Studi Pembangunan, 2014)
Abstract: This study aims to analyze the influence of world gold price, Dow Jones Islamic Market, and inflation towards the Jakarta Islamic Index (JII) in Indonesia Stock Exchange (IDX) from January 2008 to September 2013. The object of the study is publicly traded company listed on the Jakarta Islamic Index (JII). The obtained index is 30 companies listed in Jakarta Islamic Index (JII) with 69 observation data. Data analysis is performed using Error Correction Model (ECM). The result shows that whole variables have significant influence toward Jakarta Islamic Index in the long run. While in case of short run, Dow Jones Islamic Market has a significant influence toward Jakarta Islamic Index, but world gold price and inflation are not. Abstrak: Studi ini bertujuan untuk menganalisis pengaruh harga emas dunia, Dow Jones Islamic Market, dan inflasi terhadap Jakarta Islamic Index (JII) di Bursa Efek Indonesia dari bulan Januari 2008 sampai September 2013. Objek studi ini adalah perusahaan publik yang terdaftar dalam Jakarta Islamic Index (JII). Indeks yang diperoleh sebanyak 30 perusahaan dengan 69 observasi. Analisis data menggunakan Error Correction Model (ECM). Hasil menunjukkan bahwa harga emas dunia, Dow Jones Islamic Market, dan inflasi masing-masing berpengaruh signifikan terhadap Jakarta Islamic Index dalam jangka panjang. Sedangkan dalam jangka pendek, hanya Dow Jones Islamic market yang berpengaruh terhadap Jakarta Islamic Index.